IOT Network Feature Based Intrusion Detection Techniques- Review - Chaudhary, Diwakar Kumar; Yadav, Pritaj; Gupta, Sanjeev; Jha, Kanchan (2022 IEEE International Conference on Current Development in Engineering and Technology (CCET), 2022)
Communication networks become mobile and dynamic with the usage of portable wireless devices. The Internet of Things network's flexibility creates a risky environment for a variety of applications. Therefore, there is a significant possibility of an attack in such a network. In order to secure various types of networks, researchers' work in the subject of intrusion detection has been described in this paper. The architecture of the IDS was discussed as per networks with its types. Models proposed by the authors were detailed with techniques used for the detection of intrusion in different environments. The further paper has listed compared various techniques and listed strengths with limitations. Finally, evaluation parameters were listed to compare models of intrusion detection systems.